Lysophosphatidylcholine induced by fat transplantation regulates hyperalgesia by affecting the dysfunction of ACC perineuronal nets - Juan Li; Zhen Li; Yanbo Liu; Yijing Li; Yanqiong Wu; Anne Manyande; Zhixiao Li; Hongbing Xiang (iScience)
Summary: The pathogenesis of hyperalgesia is complex and can lead to poor clinical treatment. Our study revealed that epididymal white adipose tissue (eWAT) from spared nerve injury (SNI) mice is involved in the occurrence of hyperalgesia after adipose tissue transplantation. We also showed that lysophosphatidylcholine (LPC) is enriched in the eWAT of SNI mice using non-targeted metabolomic analysis and verified that the levels of LPC in plasma and the anterior cingulate cortex (ACC) region increased following eWAT transplantation. Based on the immunohistochemistry results, we observed that LPC in the ACC region activated microglia via the TRPV1/CamkⅡ pathway. Meanwhile, the disruption of perineuronal nets (PNNs) around PV+ neurons in ACC promoted hyperalgesia, and the loss of PNNs and PV+ interneurons might be due to microglial phagocytosis. These findings elucidate the mechanism underlying hyperalgesia from the perspective of lipid metabolite LPC and PNNs and provide potential strategies for the treatment of hyperalgesia.